SALINITY DISTRIBUTION IN A CHANNELIZED WETLAND AT EMILY AND RICHARDSON PREYER BUCKRIDGE COASTAL RESERVE, TYRRELL COUNTY, NORTH CAROLINA - Giuliano, Angela Simone (East Carolina University, 2014)
The Emily and Richardson Preyer Buckridge Coastal Reserve is a low-lying, peatland-dominated freshwater wetland located in the southern Albemarle Estuarine System. The construction of an extensive canal network that facilitated timber harvest and draining of adjacent agricultural lands has altered the water quality and quantity in the Reserve. Brackish conditions observed in the canal network and groundwater system of the Reserve were linked to saltwater intrusion emanating from the Alligator River. Water level, temperature, and specific conductivity data (used as a proxy for salinity) were collected to assess the quantity and quality of the groundwater and surface water system in the Reserve. The driving mechanisms responsible for spatial and temporal variations of salinity in the groundwater and surface water systems were investigated. Seasonal patterns of thermal stratification were observed in the groundwater and surface water systems. Water levels in the Reserve were affected by precipitation events and wind tide events. Specific conductivity levels in the Alligator River and canals were observed to be elevated by wind tides, which are mostly driven by strong southerly winds. The groundwater data reveal that specific conductivity levels are higher in the south of the Reserve than in the north. These observations suggest that the saltwater present in the groundwater and surface water system is emanating from south of the Reserve. The effects of a tropical storm on storm surge and saltwater intrusion in the Reserve were observed to be minimal in this study. Saltwater intrusion is a concern because it may impact the health of vegetation in the Reserve. To prevent further degradation of the environment, restoration and management efforts should focus on the use of water control structures to retard saltwater intrusion during storms and wind tides, and also account for future effects of sea level rise.
Keywords: Hydrologic sciences; Geology; Environmental geology; Buckridge; Hydrology; Salinity; Storm surge; Wetlands; Wind driven tides; Saltwater encroachment--North Carolina--Tyrrell County; Wetlands--North Carolina--Tyrrell County; Coastal zone management--North Carolina--Tyrrell County; Emily and Richardson Preyer Buckridge Coastal Reserve (N.C.)